1986
DOI: 10.1152/ajpcell.1986.250.3.c430
|View full text |Cite
|
Sign up to set email alerts
|

Mapping subcellular distribution of Na+-K+-ATPase in rat parotid gland

Abstract: Recent subcellular fractionation studies have raised the possibility that Na+-K+-ATPase might be present in both the apical and the basal-lateral membranes of exocrine gland acinar cells. Analytical fractionation and immunofluorescence microscopy studies of rat parotid glands were performed to confirm this interpretation. The distributions of biochemical markers after analyses based on differential sedimentation, equilibrium density-gradient centrifugation, and partitioning in an aqueous polymer two-phase syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…In contrast to the regulatory mechanism responsible for the acute stimulation of Na ϩ /K ϩ -ATPase transport activity, our results suggest that a separate mechanism, i.e., transporter protein translocation from an intracellular storage pool to the plasma membrane, is involved in the delayed chronic stimulation of the Na ϩ /K ϩ -ATPase transport activity (Ariyasu et al, 1985;Conteas et al, 1986;Omatsu-Kanbe and Kitasato, 1990;Yiu et al, 1988). A direct contribution of Na ϩ ,K ϩ ,2Cl Ϫ -cotransport to chronic stimulation of Na ϩ / K ϩ -ATPase transport activity was ruled out by 2 experimental results.…”
Section: Discussioncontrasting
confidence: 64%
“…In contrast to the regulatory mechanism responsible for the acute stimulation of Na ϩ /K ϩ -ATPase transport activity, our results suggest that a separate mechanism, i.e., transporter protein translocation from an intracellular storage pool to the plasma membrane, is involved in the delayed chronic stimulation of the Na ϩ /K ϩ -ATPase transport activity (Ariyasu et al, 1985;Conteas et al, 1986;Omatsu-Kanbe and Kitasato, 1990;Yiu et al, 1988). A direct contribution of Na ϩ ,K ϩ ,2Cl Ϫ -cotransport to chronic stimulation of Na ϩ / K ϩ -ATPase transport activity was ruled out by 2 experimental results.…”
Section: Discussioncontrasting
confidence: 64%
“…Studies with antibodies to rat kidney Na, K-ATPase suggested the presence in rat parotid of two distinct membrane populations enriched in enzyme activity. 9 These populations had the characteristics expected of basolateral and apical plasma membranes of acinar cells. 9 Another study using monoclonal antibodies to the P-subunit of canine Na, KATPase demonstrated relatively low levels of enzyme activity in dog parotid acinar cells, 70 but the activity was confined to the basolateral cell membrane and no activity was ascertained in apical membranes.…”
Section: Oral Biology and Medicine I The Basolateral Membranementioning
confidence: 83%
“…Na + -K + -ATPase is found in the parotid gland along the apical and basolateral plasma membranes of acinar, striated and excretory duct cells. The apical Na + -K + -ATPase is proposed to participate in series with basolateral sodium and chloride entry pathways in driving secretory electrolyte fluxes [Speight and Chisholm, 1984;Conteas et al, 1986;Simson and Chao, 1994]. Furthermore, it is suggested that in acinar cells Na + is not only transported paracellularly but is also actively transported intracellularly into the luminal space by the Na + -K + -ATPase lo- cated on luminal plasma membranes.…”
Section: Orchiectomy and Na + -K + -Atpase Activitymentioning
confidence: 99%